Armazenamento de sementes e temperatura de germinação na tolerância à termoinibição em genótipos de alface - Queiroz, Deborah Abreu (2017)
Lettuce seeds usually present germination problems that may be related to dormancy and / or temperature. Dormancy is often related to the age of the seed, when freshly harvested seeds tend to germinate little. The temperature, in turn, when in higher grades, can also reduce the germination of the seeds, the consequence of a thermoinhibition. It is known that these characteristics are also influenced by the genotype of the material. Knowing the temperature from which the thermoinhibition process begins, as well as the influence of the age of the seed on its germination, would be of great importance to establish more adequate parameters for the selection of superior genotypes in breeding programs. The objective of this work was to evaluate the germination of the seeds of three lettuce cultivars as a function of the temperature of the analysis and as a function of the age of the seeds. The Everglades cultivars were considered thermotolerant to thermoinhibition, Luisa that presented intermediate tolerance and Verônica considered thermosensitive. The seeds harvested from each cultivar were evaluated by germination test, first count, germination speed index and germination test of remaining seeds. The analyzes were performed at four temperatures of 20 ᵒC, 25 ᵒC, 30 ᵒC and 35 ᵒC and seven storage periods at 40, 70, 100, 130, 160, 190 and 260 days post-harvest. The results were submitted to analysis of variance and mean test to verify the primary dormancy and thermoinhibition in the seeds of the evaluated cultivars. Regression analysis was performed to determine the temperature that initiates the thermoinhibition process in each cultivar and to indicate the best moment of evaluation for the identification of thermotolerant genotypes. Significant differences were found in the germination of the seeds of the cultivars, according to the temperature and storage periods. It was verified that the evaluated cultivars did not present primary dormancy. Everglades seeds are tolerant to thermoinhibition with germination greater than 90% at temperatures close to 31 ᵒC. The seeds of Luisa are tolerant to thermoinhibition until temperatures close to 29,5 ᵒC, when they still present germination near 90%. And the seeds of Verônica present tolerance to thermoinhibition, until 29 ᵒC. The temperature at which the thermoinhibition process begins in lettuce seeds is 29.5 ᵒC. The identification of lettuce genotypes tolerant to thermoinhibition should be performed on seeds from 260 days after harvest.